Oral Bioavailability and Pharmacokinetics of Trovafloxacin in Patients with AIDS - Lacy, Melinda K. (American Society for Microbiology, 1999)
Trovafloxacin pharmacokinetics were evaluated in 12 subjects with AIDS. By using a randomized design, single 200-mg doses of oral trovafloxacin and intravenous alatrofloxacin were administered. The mean absolute bioavailability was 91%. The pharmacokinetics of trovafloxacin when administered orally as the active form or intravenously as the prodrug (alatrofloxacin) are not altered in subjects with AIDS compared to those in healthy adults.